Preparing students for diverse careers in the poultry industry - Elizabeth L. Karcher; J. Marcos Fernandez; Christine Z. Alvarado; Nada Tamim; Drew Benson (Poultry Science)
Symposium Summary: Careers in the poultry industry are ever evolving to address global challenges and include collaborations with others from diverse backgrounds and cultures from around the world. Employers are seeking college graduates who are prepared to use novel approaches to address local and global industry challenges. A primary goal of undergraduate animal and poultry science programs should be to focus on courses and opportunities for students to engage in activities that promote workforce and essential skill development. A symposium at the 2024 Poultry Science Association annual meeting included a unique perspective from academic and industry professionals on the essential skills needed by graduates to be most successful in the industry. This paper is a summary of the symposium's presentations concerning workforce development.